Evaluasi Program Desa Wisata Candirejo Dalam Upaya Peningkatan Kesejahteraan Masyarakat Desa Candirejo, Kecamatan Borobudur, Kabupaten Magelang - -, Riangger; Subowo, Ari; Herawati, Augustin Rina (Journal of Public Policy and Management Review, 2024)
Tourism sector is used as an effective means of encouraging regional development. The government initiated the Tourism Village Program as a strategic effort to empower the community through the tourism sector. Candirejo Tourism Village is the first tourist village in Magelang Regency as well as pilot project tourist village in Magelang Regency. However, Candirejo Village still has a high number of underprivileged families, there are many people who dont have jobs. So, this research aims to examine and analyze program evaluation as well as supporting and inhibiting factors in implementing the Candirejo Tourism Village Program. This research use a qualitative descriptive method through evaluation measures according to Kendall (1992). Indicators of Measurement Result, Cost Efficiency, Organizational Change and Unplanned Effect has been able to have a positive influence and bring situation changes for some people in Candirejo Village. Meanwhile on indicators Goal Achievement, Measurement of Improvement, Unarticulated Hopes has not been able to achieve all of the program objectives and there are still program targets who are not participating. The supporting factors for implementing the Candirejo Tourism Village Program are communication, community participation and resources, while the inhibiting factors related to the organizational structure which still needs to be improved.